2011
DOI: 10.1111/j.1756-185x.2010.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic‐musculoskeletal manifestations in type 2 diabetes mellitus patients in south India

Abstract: Thorough RMS examination should be included as an integral part of care in T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 16 publications
7
44
2
Order By: Relevance
“…A study conducted in USA [3] showed only longer duration of DM had association with the presence of shoulder and hand complication. Similarly a study done in Kerala, India identified a higher frequency (52.9%) of DM of more than 5 years duration [16]. In contrast to previous studies that found duration of diabetes to be significant, this study showed no significant association between the occurrence of shoulder and hand complications and duration of DM in a multivariate logistic regression model.…”
Section: Doi: 107243/2050-0866-2-8contrasting
confidence: 97%
“…A study conducted in USA [3] showed only longer duration of DM had association with the presence of shoulder and hand complication. Similarly a study done in Kerala, India identified a higher frequency (52.9%) of DM of more than 5 years duration [16]. In contrast to previous studies that found duration of diabetes to be significant, this study showed no significant association between the occurrence of shoulder and hand complications and duration of DM in a multivariate logistic regression model.…”
Section: Doi: 107243/2050-0866-2-8contrasting
confidence: 97%
“…In contrast, Aydeniz and cols. (13) found a prevalence of 14.7% in 102 diabetic frozen shoulder; Mathew and cols., reported a similar finding in 16.4% (14) of their patients; and Ramchurn and cols. (15), in 25% of their 96 patients.…”
Section: Referencessupporting
confidence: 59%
“…8 Other studies suggest an association between diabetes and musculoskeletal disease. 9 Statin use has been implicated as a possible risk factor for tendon disease, including tendon rupture and tendinitis, and shoulder stiffness. 10,11 The extent of this risk and the influence of gender is not clear.…”
Section: Discussionmentioning
confidence: 99%